The Influence of Internal Environment, Strategic Management of Human Resources and Quality of Work Life To Job Satisfaction and Employee Performance Outsourcing Company in East Java Province - Soemantri, Asep Iwa; ., Misdah (Archives of Business Research, 2019)
The company is getting tougher competition pushed companies to do innovation and efficiency. Companies that are able to produce with efficient cost and products that have the innovation will be able to compete. But for companies that are not able to compete will be gradually eliminated so that it can cover does not operate. The competition also demands the development of human resources and improving the management of the company to be more advanced. The company became the winner is the company that applied the human resources development and the status of management so efficient. The purpose of this research is to examine and analyze the effect of the internal environment, management stategik human resources and quality of work life to job satisfaction and employee performance outsourcing company in East Java Province. The technique used is the analysis of path analysis with Structural Equation Modeling with the program SPSS version 23 and AMOS 18. The population in this research is the employee performance outsourcing company in East Java Province and sample numbering 185 employees. The results of the discussions can be concluded that Internal Environment effect significantly to job satisfaction, Strategic HR management effect significantly to job satisfaction, Quality of_work life effect significantly to job satisfaction, Internal environmental effect significantly to performance of employees, Strategic HR management effect significantly to performance of employees, Quality of_work life effect significantly to performance of employees and Job satisfaction effect significantly to performance of employees.